Large-scale atomistic simulations of CNT-reinforced thermoplastic polymers. (1st May 2018) - Alian, A.R.; Meguid, S.A.
Graphical abstract: The mechanical properties of CNT-reinforced composites at the bulk level were obtained in this study using large-scale molecular dynamics simulations of representative volume elements reinforced with CNTs of different morphologies, lengths, and bundle sizes. Abstract: Different multiscale techniques were developed over the past two decades for modeling CNT-reinforced composites. However, these techniques contained numerous approximations to allow scaling up the properties from nanoscale to bulk levels. These approximations were partly responsible for the anomaly between model predictions and experiments. In this study, we overcame this problem by modeling large (up to one million atoms) representative volume elements (RVEs) reinforced by CNTs with different lengths (aspect ratio up to 500), curvatures (ranging from straight to severely curved) and bundle sizes to simulate actual nanocomposites. The RVE dimensions were carefully selected to ensure that the molecular structure of the nanocomposite is successfully represented and the obtained elastic properties are independent of the RVE size. A series of extensive MD simulations were conducted to determine the elastic moduli of the nanocomposite using the constant-strain energy minimization method. The developed models were verified by comparing their predictions with the reported experimental results. The developed MD models were further used to study the effect of CNT morphology and the state of dispersion on the elastic moduli of CNT-polyethylene composite. The current model can be integrated with electrical and thermal models to predict the multifunctional properties of CNT-reinforced composites.